2017
DOI: 10.1016/j.ejca.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industry collaboration on randomised controlled trials in oncology

Abstract: Background Industry funders can simply provide money or collaborate in trial design, analysis, or reporting of clinical trials. Our aim was to assess the impact of industry collaboration on trial methodology and results of randomized controlled trials (RCT). Methods We searched PubMed for oncology RCTs published May 2013 to December 2015 in peer-reviewed journals with impact factor > 5 requiring reporting of funder role. Two authors extracted methodologic (primary endpoint; blinding of the patient, clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
27
1
1
Order By: Relevance
“…Publications on strategies to improve recruitment rates, to retain participants in clinical research, and to facilitate researcher‐clinician collaboration reported difficulties in combining clinical and research roles, where the main reasons were the lack of time, ethical concerns, and absence of leadership, particularly in the field of nursing . The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration . However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications on strategies to improve recruitment rates, to retain participants in clinical research, and to facilitate researcher‐clinician collaboration reported difficulties in combining clinical and research roles, where the main reasons were the lack of time, ethical concerns, and absence of leadership, particularly in the field of nursing . The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration . However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management.…”
Section: Introductionmentioning
confidence: 99%
“…33 The discussed models of combining clinical and research activities in various health fields were collaboration, partnership, and integration. [34][35][36][37] However, the process of routinisation of RCTs in clinical practice has not been discussed as a holistic process and as a separate model, including in the field of wound management. In this article, we have developed the Routinisation of Trials Framework, analysing practical suggestions offered by clinical and research nurses from the Australian wound clinics.…”
Section: Introductionmentioning
confidence: 99%
“…These can be directly NIH/ NCI funded or pharmaceutically funded as long as the concept originated with the investigator. 4 Taking a compound from discovery, to understanding the mechanism of action, to phase 1 testing is the highlight of a solid experimental therapeutics program. This is a key focus of investment for institutional and philanthropic dollars.…”
mentioning
confidence: 99%
“…The subsequent trials methodology must be strong. Some studies report industry collaboration trials were more likely to use high-quality methods than trials without industry funding [3]. Other reports found limited but important differences; industry studies were more likely to be at low risk of bias because of blinding but more likely to yield conclusions that did not align with the results compared with non-industry studies [2].…”
mentioning
confidence: 99%
“…Unit, Imperial College Healthcare NHS Trust, St Mary's Hospital, London, UK. 3 Centre for Heart Lung Innovation (HLI), Vancouver, Canada. 4 Division of Critical Care Medicine, St. Paul's Hospital, University of British Columbia, 1081 Burrard Street, Vancouver, BC V6Z 1Y6, Canada.…”
mentioning
confidence: 99%